Tobacco Use Among People Who Have Been in Prison: Relapse and Factors Associated with Trying to Quit. (16th March 2016) - Frank, Michael R.; Blumhagen, Rachel; Weitzenkamp, David; Mueller, Shane R.; Beaty, Brenda; Min, Sung-Joon; Binswanger, Ingrid A.
Abstract : Introduction: Tobacco use is common among people who have been in prison. The relationship between social stressors, risky health behaviours, and smoking cessation has not been studied in people recently released from prison. Studying this relationship could yield information that guides strategic and cost-effective tobacco cessation interventions for an under-resourced population. Methods: One hundred and forty-three smokers were interviewed 7 to 21 days after they had been released from USA prisons. Independent variables included employment status, housing security, relationship problems, educational achievement, risky drinking behaviour, recent drug use, history of drug dependence, and depression. The primary outcome was 'trying to quit smoking.' Data were analysed using Pearson chi-square tests and single and multivariable logistic regression models. Results: Of those who had to quit smoking due to tobacco-free prison policies, 98% reported relapsing on tobacco after release. Trying to quit smoking was associated with the absence of risky drinking behaviour in the past 30 days (adjusted odds ratio [AOR] 6.44, 95% confidence interval [CI] 2.02–20.48). Conclusions: The absence of risky drinking behaviour is associated with trying to quit smoking among people recently released from prison. Further research may determine whether interventions addressing risky alcohol use can reduce smoking relapse.